Spirulina platensis mitigates the neuroinflammatory effect of LPS-Induced BV2 Microglia - Ngu, Ee Ling (2021)
Neurodegenerative diseases are diseases attributable to neuronal loss through progressive degeneration, and one of the pathophysiologies is neuroinflammation. As one of the neuroinflammation regulatory cell, uncontrolled microglia activation promotes excessive secretion of proinflammatory mediators that will lead to neuronal cell death in neurodegenerative diseases. Current therapeutic options can only alleviate symptoms and were accompanied by multiple adverse effects. Furthermore, the socio-economic burden caused by neurodegenerative disease also increases due to an increase in life expectancy. Therefore, research efforts have been focusing on the discovery of potential therapeutic agents from natural resources for minimal adverse effects. Antioxidative and anti-inflammatory activities of S. platensis give rise to protection on dopaminergic neurons. In addition, S. platensis alleviates the morphological impairment on spinal cord and aids in the post-injury recovery. Therefore, we hypothesise that S. platensis UMACC 159 extracts can promote anti-neuroinflammatory activity by attenuating the lipopolysaccharide (LPS)-stimulated neuroinflammation in BV2 microglia. Objectives of this study include: (1) to investigate the presence of phytochemical constituents and antioxidant capacity of S. platensis UMACC 159 extracts; (2) to study the anti-neuroinflammatory effect of S. platensis UMACC 159 extracts in LPS-induced BV2 microglia; and (3) to determine the potential bioactive compound(s) profile of the most potent S. platensis UMACC 159 extract using Liquid Chromatography-Mass Spectrometry (LC-MS). S. platensis UMACC 159 culture strain was obtained from the Algae Research Laboratory in the University of Malaya. Four S. platensis UMACC 159 extracts (hexane, ethyl acetate, ethanol, and water) were screened for total phenolic content (TPC) and total flavonoid content (TFC) using Folin Ciocalteu reagent and aluminium chloride respectively. Antioxidant capacity of all extracts were determined using 2,2’-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-Diphenyl-1-pircrylhydrazyl (DPPH) and reducing power. Cell-based assays using BV2 microglia were used to screen for (1) the effect on cell viability via 3-(4,5-dimethylthiazol-2-yl)-2,5-iphenyltetrazolium bromide (MTT) assay and (2) the NO inhibitory activity via Griess assay. Ethanol extract with the highest antioxidative and NO inhibitory activities was selected for subsequent study on (1) the production of PGE2, IL-6 and TNF-α by BV2 microglia using ELISA, and (2) the protein expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) by BV2 microglia using western blot. The list of compound(s) present in ethanol extract was tentatively identified via LC-MS and the potential bioactive compounds related to neurodegenerative disease were identified based on literature search. Screening of the four S. platensis UMACC 159 extracts demonstrated that ethanol extract had the highest flavonoid content, antioxidative and NO inhibitory activities. Ethanol extract inhibits the NO production via downregulation of iNOS and reduces TNF-α and IL-6 secretion. LC-MS analysis revealed that ethanol extract contained 35 compounds, with 21 compounds being identified and 14 compounds remaining unknown. Based on literature search, emmotin A, palmitic amide, and 1-monopalmitin were proposed as the bioactive compounds in ethanol extract. In conclusion, S. platensis UMACC 159 ethanol extract possess neuroprotective property through antioxidative and anti-neuroinflammatory mechanisms, with emmotin A, palmitic amide, and 1-monopalmitin being the potential bioactive compounds. The current study would certainly contribute to the identification of bioactive compound(s) for the development on functional food targeting neurodegenerative disease. However, further isolation and bioassay-guided identification on the bioactive compound(s) are essential to conclude the identity of the bioactive compound(s) that contribute to the neuroprotective activity of S. platensis UMACC 159 ethanol extract. In addition, molecular study on the signalling pathway(s) involved in the neuroprotective activity of ethanol extract is also important in the effort of managing neurodegenerative disease with complex pathologies, as the signalling pathway(s) may be involved in more than one of the pathological processes in neurodegenerative disease.